PENGARUH DIMENSI KOMPENSASI TERHADAP MOTIVASI DAN KINERJA MARKETING UMKM DI WILAYAH YOGYAKARTA - Dodi Setiawan Riatmaja; Rahma Widyawati (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2022)
The purpose of this study was to determine the effect of the compensation dimension on the motivation and performance of MSME marketing employees in Yogyakarta. This research was conducted by taking 54 MSME employees in Yogyakarta randomly as many as 54 MSME marketing employees. The calculation technique used in this study is the Multiple Linear Regression Analysis model and path analysis. Based on the analysis results indicate that there is a significant influence between the dimensions of compensation on motivation; there is a significant effect between compensation on employee performance. Overall indirect effect, then incentive compensation is the variable with the strongest influence on performance through work motivation variables. It can be explained that incentives are the driving variables for increasing work motivation and performance because a lot or less of their income is very dependent on whether or not incentives are good. Simultaneously, the compensation system for salaries, incentives, and benefits has a strong influence on performance through work motivation, with a total determination coefficient is 0.822.